PENERAPAN SAPTA USAHA TERNAK AYAM BROILER BERDASARKAN PENDIDIKAN PETERNAK - Yuman Panju; Suparmin Fathan; Sry Yenny Pateda; Fahria Datau (xxxx-xxxx, 2022)
The purpose of the study was to determine the level of application of Sapta Usaha on broiler breeders through a partnership pattern. The research was carried out for two months from December to February 2022. It was carried out in three broiler farms located in Tilongkabila, Kabila and Tapa sub-districts. The average age of broiler breeders is between 16-65 years and is included in the productive category. Breeder education, high school education, bachelor's, and master's degree. The application of the SAPTA for broiler business as a whole shows a very good value in applying the SAPTA for the livestock business with a score of 44.8 and the breeders apply the livestock business activities.